A Branch-and-Prune algorithm for the Molecular Distance Geometry Problem - Liberti, Leo; Lavor, Carlile; Maculan, Nelson (International transactions in operational research, 2008)
The Molecular Distance Geometry Problem consists in finding the positions in of the atoms of a molecule, given some of the inter‐atomic distances. We show that under an additional requirement on the given distances this can be transformed to a combinatorial problem. We propose a Branch‐and‐Prune algorithm for the solution of this problem and report on very promising computational results.